Tata Kelola Kolaboratif dalam Pengelolaan Sampah Plastik: Studi Kasus di Kabupaten Lamongan - Wartono, Wartono; Erison, Yendra; Rohmah, Eva Nur Laily (Journal of Social Movements, 2025)
The problem of plastic waste is a crucial issue facing many regions, including Lamongan Regency, which experiences a significant increase in waste volume each year. Despite management programs, such as "Green Lamongan," environmental problems persist due to limited infrastructure, low public awareness, and weak collaboration between stakeholders. This study aims to analyze the forms of collaboration between local governments and local communities in plastic waste management and identify the challenges and impacts of these programs. The method used was descriptive qualitative, with data collected through interviews, observations, and documentation studies from official government sources and online media. The results show that initiatives such as the "Berkah Mandiri" Waste Bank and the "Sampahku Tanggungjawabku" (My Waste is My Responsibility) program (Samtaku) have contributed significantly to promoting a circular economy, reducing waste volume, and increasing community participation. These programs have generated economic value of up to IDR 5 billion per year and opened recycling-based business opportunities. However, challenges remain, such as a lack of facilities, suboptimal inter-agency coordination, and community resistance to behavioral change. In conclusion, strong collaboration, ongoing education, and infrastructure support are the keys to the success of participatory and sustainable plastic waste management in Lamongan Regency.